MORPHOMETRIC, PONDERAL AND VOLUMETRIC STUDY ON NESTS OF HYPODYNERUS CHILIENSIS (LEPELETIER). (HYMENOPTERA: EUMENIDAE) (Acta Entomológica Chilena, 2022)
A study on form, weight, volume and lineal measures of nests of the masón wasp Hypodynerus chiliensis(Lepeletier) of central Chile is presented.